Understanding Terrorism : Analysis of Sociological and Psychological Aspects. - Ozeren, Suleyman (NATO Science for Peace and Security Series: Human and Societal Dynamics, v. 22., 2007)
Terrorism is a multi dimensional phenomenon and this publication aims at comprehending it. It includes a comprehensive focus on the conceptualization of terrorism and understanding of it. It explains the concept and addresses the important issues which can help us to understand why and how individuals commit such an act.